The new class - Sturges, Lilah (Archaia, 2020)
Long after Quentin and his friends have graduated from Brakebills College for Magical Pedagogy, Dean Fogg invites a historic new group of students to enroll<U+2013> the first ever class of hedge magicians, rogue practitioners of unsanctioned magic. But the traditional magicians aren<U+2019>t too thrilled to have the rule-breaking outcasts in their hallowed halls, and tempers flare as the student bodies clash to prove their superiority <U+2013> not realizing a new danger has emerged to threaten them all. The malevolence behind the threat at Brakebills will rock everyone to their cores <U+2013> and even shock longtime fans of The Magicians!